The quality of life of home-ventilated children and their primary caregivers plus the associated social and economic burdens: a prospective study. Issue 7 (3rd March 2016) - Seear, Michael; Kapur, Akshat; Wensley, David; Morrison, Kelly; Behroozi, Ariana
Abstract : Background: Despite the obvious challenges faced by families caring for children on home ventilation, there is surprisingly little research into the details of their daily lives. In particular, little is known about the quality of life of the child and caregiver plus the associated social and economic burdens of care. Methods: We prospectively studied 90 families enrolled in a paediatric home ventilation service in British Columbia. In the clinic, we recorded demographic information, patient acuity score and quality of life for patient and caregiver using standardised questionnaires. Parents then monitored social and financial costs of care at home over the subsequent 8 weeks. These data were collected by telephone at 1 and 2 months. Results: Most children led rich active lives. Camping trips, wheelchair sports and foreign travel were the norm, not the exception. Over 90% assessed the burden of care as mild or moderate. Government support covers medical expenses and home nursing (median 32 h/week, IQR 0–62.5 h). Monthly unreimbursed family expenses were low (median 87.7, IQR 15.3–472). Despite this, nearly 25% of primary caregivers assessed burden of care as severe and over 50% had chronic illnesses requiring daily medication (principally depression, anxiety and arthritis). Quality of life for children or caregivers did not correlate with income or education. Interpretation: Home ventilation of complex children is a successful strategy but it places significant strain on the primary caregiver. Specific attention to the physical and mental health of the caregiver should be an integral part of the management of home-ventilated children. Trial registration number: NCT01863992.